The Explosive Sensitivity on the Complex Formation of 3-Nitro-1,2,4-Triazol-5-One and Metal Ions Based on Density Functional Study - Hadisaputra, Saprizal; Prasetyo, Niko (UI Scholars Hub, 2016)
The explosive sensitivity upon the formation of supramolecular interaction between the nitro group of 3-nitro-1,2,4-triazol-5-one (NTO) and metal ions (Mn+ = Li+, Na+, Be2+ and Mg2+) has been investigated using Density Functional Theory at B3LYP/6-311++G** level of theory. The bond dissociation energy (BDE) of the C1–N6 trigger bond has also been discussed for the NTO monomer and the corresponding complexes. The interaction and bond dissociation energy of the C6–N7 trigger bond follow the order of NTO-Be2+ > NTO-Mg2+ > NTO-Li+ > NTO-Na+ > NTO monomer. The enhancement of the trigger bond dissociation energy in comparison with the NTO monomer correlates well with the complex interaction energies, trigger bond length, and charge transfer. The analyses of electron density shifts have shown that the electron density of the nitro group shifts toward the C1–N6 trigger bond upon the formation of the supramolecular interaction. As result, the trigger bond is strengthened and the sensitivity of NTO is reduced. Some of the calculated results agree with the experimental values.